2019
DOI: 10.1038/s41419-019-1833-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cysteine oxidation on DJ-1 cytoprotective function in human alveolar type II cells

Abstract: DJ-1 is a multifunctional protein with cytoprotective functions. It is localized in the cytoplasm, nucleus, and mitochondria. The conserved cysteine residue at position 106 (Cys106) within DJ-1 serves as a sensor of redox state and can be oxidized to both the sulfinate (-SO 2 − ) and sulfonate (-SO 3 − ) forms. DJ-1 with Cys106-SO 2 − has cytoprotective activity but high levels of reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 68 publications
(89 reference statements)
4
35
0
Order By: Relevance
“…Likewise, when parkin is sulfonated, this protein becomes insoluble, probably linked to neuronal dysfunction [ 43 ]. The other protein, Dj-1's sulfonation has been also reported to lose cytoprotective function [ 44 ]. Under severe stress, the Xbp-1 splicing might be overwhelmed/overcome by the parallel RNA decay process [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, when parkin is sulfonated, this protein becomes insoluble, probably linked to neuronal dysfunction [ 43 ]. The other protein, Dj-1's sulfonation has been also reported to lose cytoprotective function [ 44 ]. Under severe stress, the Xbp-1 splicing might be overwhelmed/overcome by the parallel RNA decay process [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that DJ-1 protein can be used as a reactive oxygen scavenger and can remove hydrogen peroxide through self-oxidation in vitro cell models ( Taira et al, 2004 ), thus protecting mitochondria from damage. In addition, under the stimulation of oxidative stress, DJ-1 protein can not only prevent the activation of apoptosis pathway by oxidizing its own Cys106 ( Bahmed et al, 2019 ), but also reduce the expression of Bax protein by reducing the transcriptional activity of p53, and then inhibit the apoptotic pathway of Bax-caspases, thus protecting mitochondrial function ( Salah et al, 1995 ). The overexpression of DJ-1 protein can protect cells, enhance the tolerance of cells to toxins, and reduce mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%
“…Since highly reactive Cys46 does not undergo various oxidation [39], it is possible to form a disulfide bond. To investigate whether Cys46 could form a disulfide bond, we examined the electrophoretic mobility of WT and mutant DJ-1s on SDS-PAGE with or without 2-mercaptoethanol (β-ME) ( Fig.…”
Section: Cys46 and Cys53 Form An Intra-disulfide Bond In Vitromentioning
confidence: 99%